Desenvolvimento e testes in vitro e in vivo de um Hidratante e fotoprotetor a base de óleo de amêndoas de Attalea speciosa (Babaçu) para xerose cutânea em pacientes com Hanseníase - SILVA, Michael Jackson Ferreira da (2019)
Cutaneous xerosis (CX) is a change in the stratum corneum (SC) characterized by reduced proliferation and differentiation of keratinocytes, lipid content, hydration, pH and sebum production. Evidence suggests that the composition and amount of SC lipids from leprosy patients are different from those of healthy individuals. Several products derived from vegetables have been studied as candidates for moisturizers, with emphasis on babassu coconut almond oil (Attalea speciosa), one of the most important representatives of Brazilian palm trees. In this way a cream-gel formulation was developed using babassu coconut oil as an emollient and occlusive active in the reduction of CX in leprosy patients in the state of Maranhão. . The physicochemistry and chromatography were analyzed by Gas Chromatography Coupled to Mass Spectrometry (CG-MS) of the babassu oil sample. Development and quality control of the formulation. Selection of volunteers treated or being treated for leprosy from 2015 to 2018 in Buriticupu – MA. The clinical trials were performed in two 15-day cycles: first with the cream-gel formulation with babassu oil (treatment A) and the second with the gel-cream formulation without babassu oil (treatment B). A control (untreated) area was included in both cycles. Biometric evaluations were performed on days (D0, D7 and D15) for the comparative effect of the results. Biophysical evaluations were performed using Corneometer® and SkinpHmeter®. The results of the physico-chemical analysis of unmanufactured and unfiltered babassu coconut oil (OBNAnF) showed reduced acidity, saponification and density indices, and refraction within the national and international standards. Transesterification of the OBNAnF sample analyzed by GC-MS demonstrated the predominance of lauric acid, followed by myristic acid. Treatment A showed the best moisturizing capacity (29.4 ± 0.6) when compared to treatment B (25.1 ± 0.1) and control (25.4 ± 0.9), in the first week (D7). At week D15, treatment A (29.07 ± 0.7) also showed the best hydration capacity, compared to treatment B (26.5 ± 1) and control (23.3 ± 0.1). The results of weeks D7 and D15 presented statistical significance (p = 0.0140). The cream-gel formulation did not significantly alter the pH of the volunteers' xerotic skin, treatment A (11.6 ± 0.1), treatment B (8.8 ± 0.2) and control (11, 4 ± 0.2) at week D7 when compared to week D15, treatment A (11.0 ± 0.4), treatment B (11.6 ± 0.1) and control (11.4 ± 0.2). Therefore, the results of the clinical evaluations show the efficacy and good tolerability of the formulation in the hydration of the xerotic skin. The biophysical evaluation of the cream-gel formulation showed a significant improvement in the skin moisture.